Open innovation and the evaluation of internet-enabled public services in smart cities. (December 2018) - Paskaleva, Krassimira; Cooper, Ian
Abstract: This article is focused on public service innovation from an innovation management perspective. It presents research experience gained from a European project for managing social and technological innovation in the production and evaluation of citizen-centred internet-enabled services in the public sector. It is based on six urban pilot initiatives, which sought to operationalise a new approach to co-producing and co-evaluating civic services in smart cities – commonly referred to as open innovation for smart city services. Research suggests that the evidence base underpinning this approach is not sufficiently robust to support claims being made about its effectiveness. Instead evaluation research of citizen-centred internet-enabled urban services is in its infancy and there are no tested methods or tools in the literature for supporting this approach. The paper reports on the development and trialing of a novel Co-evaluation Framework, indicators and reporting categories, used to support the co-production of smart city services in an EU-funded project. Our point of departure is that innovation of services is a sub-set of innovation management that requires effective integration of technological with social innovation, supported by the right skills and capacities. The main skills sets needed for effective co-evaluation of open innovation services are the integration of stakeholder management with evaluation capacities. Highlights: Public sector service development should be treated as a distinct subset of innovation management. Co-production and co-evaluation of smart city services are parallel, interactive processes. Evaluation of smart city services requires effective integration of technological and social innovation. Living labs require stakeholder engagement throughout the entire life cycle of services development. Managers need skills to integrate stakeholder management effectively with co-evaluation.